An investigation into the force-EMG relationship for static and dynamic exertions - Koekemoer, Wesley Agosthinho (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
The force-EMG relationship has multiple applications in varying fields of study and practice. One such application is the development of safety guidelines and regulations. Current guidelines are based on static muscle actions even though the majority of tasks encountered in industry are dynamic in nature. This may have negative implications for the health, safety, and productivity of workers as regulations based on static muscle actions may place higher force demands on manual labourers compared to what would be expected if regulations were based on dynamic muscle actions. Regulations based on dynamic muscle actions may be more effective in worker safety as the nature of the regulation matches that of the demand. Few studies have investigated the force-EMG relationship during dynamic muscle actions and the few that do exist have reported contradictory / mixed results. Therefore, the purpose of this study was to: 1) gain an understanding of EMG responses at different load levels, and 2) show how the relationship differs between static and dynamic muscle actions. A two-factorial repeated-measures experiment was developed for this study. Eighteen experimental conditions, utilizing six load levels (0%, 20%, 40%, 60%, 80%, and 100% of maximum voluntary force) for each of the three muscle actions (isometric, concentric and eccentric). Surface EMG responses were obtained under these conditions by repeatedly dorsiflexing and plantarflexing the foot, thus activating the soleus muscle. A maximum voluntary exertion on an isokinetic dynamometer determined the maximum force level, based on which the sub-maximal loads were calculated and added to a pulley system. 31 student participants were recruited for this experiment which was conducted over two sessions "“ one information and habituation session, and one experimental session. The EMG data recorded were processed and checked for normality and outliers. The data was then analysed via a General Linear Model analysis to determine the effect of exertion type and of load level on the muscle activity. Significant differences were identified at p<0.05 and followed by a Tukey post-hoc test. Correlation analyses were also conducted to determine the relationship between the force and EMG at all three exertion types. All dependent measures showed that as the load level increased so did the sEMG amplitude for all muscle actions. Muscle actions differed significantly between majority of six force levels. Correlations between the load levels and sEMG amplitude for each muscle action indicated a significant correlation with a moderate strength. The conclusion draws from this study that there is a positive correlation between force and sEMG amplitude, at all load levels, with a moderate strength. However, the muscle actions differed significantly from each other.
Keywords: Electromyography; Force and energy; Muscles Physiology; Biomechanics; Muscle contraction; Isometric exercise; Isotonic exercise; Static and dynamic exertions